Assessing agricultural gene editing regulation in Latin America: an analysis of how policy windows and policy entrepreneurs shape agricultural gene editing regulatory regimes - Zarate, Sebastian; Cimadori, Ilaria; Jones, Michael S.; Roca, Maria Mercedes; Barnhill-Dilling, S. Kathleen (Frontiers in Bioengineering and Biotechnology, 2023)
This article explores the new developments and challenges of agricultural Gene Editing (GED) regulation in primarily ten countries of Latin America and the Caribbean (LAC) Region: Argentina, Bolivia, Brazil, Colombia, Guatemala, Honduras, Mexico, Panama, Paraguay and Peru. As GED technology develops, LAC regulatory regimes struggle to keep pace. Developers and regulators face challenges such as consumer perceptions, intellectual property, R&D funding (private & public), training, environmental and social impact, and access to domestic and international markets. Some LAC countries have implemented new regulations to differentiate GED assessment pathways from transgenics, while others have adapted existing legislation. Other countries such as Peru have opted to ban the technology due to its perceived resemblance to transgenic Genetically Modified Organisms (GMOs). After presenting the regulatory landscape for agricultural GED in LAC, this article addresses some of the differences and similarities across the region. Some countries have had more foresight and have dedicated resources to increase capacity and develop regulations while others struggle with bureaucratic limitations and partisanship of policymaking. We propose that the differences and similarities between these regulatory regimes have emerged as a result of policy entrepreneurs (influential individuals actively involved in policy making) taking advantage of policy windows (opportunities for shaping policy and regulation). The third and remaining sections of this study discuss our main findings. Based on 41 semi-structured interviews with regulators, scientists, product developers and activists, we arrived at three main findings. First, there seems to be a consensus among most regulators interviewed that having harmonized regimes is a positive step to facilitate product development and deployment, leading to commercialization. Second, reducing bureaucracy and increasing flexibility in regulation go hand in hand to expedite the acquisition of reagents required by developers in countries with less robust regimes. Finally, developing public and private partnerships, fostering transparency, and increasing the involvement of marginalized groups may increase the legitimacy of GED regulation.